(3JMaI GdWGdH HeYQaI CMGOjK GHf GdMGLHs - (3ESeGYjd Hf YeQ Hf cKjQ Hf Vqh Hf OQY GdbQTj GdHUQhj Ke GdOeTbqj, CHh GdaOGA, YeGO GdOjf,J (B774 (3g` s; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s ((3eMeO Hf CMeO Hf XgjQ s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO aEf Gddg JYGdi jbhd ai cJGHg GdYRjR (B( (3hJYGhfhG Ydi GdHQ hGdJbhi hdG JYGhfhG Ydi GdEKe hGdYOhGf Cfi bQCJ GdcJGH GdeNJUQ GdUZjQ ai GUhd Gdabg ddTjN GHf GdMGLH QMeg Gddg hgh cJGH fajS LOkG s
(3BNQgG (B:s
(3Gf GdfHi Udi Gddg Ydjg hSde (B" (3deG ONd GdHjJ OYG ai fhGMjg cdgG hde jUd ajg MJi NQL adeG NQL QcY ai bHd GdHjJ QcYJjf hbGd gPg GdbHdI bdJ dg eG jhGLgG Edi RhGjGgG bGd Hd cd bHdI ef GdHjJ QhGg eSde BNQ GdJYdjb hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3HgG hbajIs
(3Ydjg JhbjY TgGH GdOjf CMeO Hf GdedG hhdOg GHQGgjes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs